Avaliação de um estudo de caso de inércia de máquinas utilizando programa computacional de engenharia - Santos, Leonardo Sousa (2019)
CAD/CAE programs are a great help to the engineer, bringing economy and agility to the project, through the possibility of performing simulations, mitigating the need of prototypes. In the field of mechanical designs, the inertia of the machine is important to determine the drive and braking torque required in the engine of a load vehicle, in addition, the rolling resistance, defined as friction generated due to deformation that the wheel suffers when in contact with the surface, is a parameter often ignored in determining the inertia. In this work, the Motion supplement of the Solidworks® program was used to evaluate the case study of a four-wheeled inclined-plane loader driven by a belt drive connected to the rear axle which was evaluated by accelerating on an ascent and braking on a descent, considering the rolling resistance. A validation of the program was performed where satisfactory results were obtained, but there was a need for an iterative method to circumvent limitations of the program that does not consider the deformation of the wheel in its calculations and considers the contact area in the calculation of the frictional force coming from a bearing. When comparing the results of the program to the analytical results of the case study, there was a relatively large error between the normal reaction values. In the actuation torque, braking torque and acceleration, the error was within the tolerance of 1%. Finally, it was found analytically that the contribution of rolling friction in determining the drive torque becomes significant when the materials allow a greater deformation in contact, as the case between tire and asphalt.